POLISI LALU LINTAS DI KOTA SEMARANG BERISIKO OBESITAS - Emy Herliani; Muhammad Saleh; Sakundarno Adi; Anies Anies; Bagoes Widjanarko; Suharyo Hadisaputro; Sumy Hastry Purwanti (Universitas Pekalongan, 2015)
Obesity is a condition due to the imbalance of calories in the body. Obesity which appears in adolescence tend to continue into adulthood, and until the elder years. The purpose of this study is to determine the influence of obesity risk factors in traffic police.Methods : The design used case-control. The number of respondents were 90, which consist of 45 cases and 45 controls, which were selected using simple random sampling. Bivariate data analysis used chi-square and multivariate used logistic regression.Results : Two variables that were significantly associated are excessive calorie intake rate (OR = 10.95 and 95% CI = 3.22 to 37.16) and lack of physical activity (OR = 3.78 and 95% CI = 1.04 to 13 ,66). If respondents possess both of the factors, chances for obesity will equal to ( 88 % ).Conclusion : Risk factors are excessive calorie intake rate and lack of physical activity. It is expected to increase the role of leaders and institutions involved in the promotion of healthy living and obesity prevention through socialization. Keywords : Obesity, risk factors, excessive calorie intake rate, lack of physical activity